A better research-practice partnership. (November 2016) - Henrick, Erin; Munoz, Marco A.; Cobb, Paul
District leaders often feel that working with researchers is not mutually beneficial. Researchers don't provide enough practical guidance, and they're often unable to present their findings in time to inform district decision making. Research-practice partnerships (RPPs) are a potential new strategy for addressing these challenges. RPPs are long-term, mutual collaborations between practitioners and researchers that are organized to investigate problems of practice and solutions for improving district outcomes. By focusing on real-time district challenges, RPPs can lead to research that is informative, timely, and relevant to district stakeholders .